Increased secreted PLA2 in epithelial cells promotes the progression of chronic non-atrophic gastritis to chronic atrophic gastritis through the TGF-β signaling - Hairong Hao; Yanjun An; Yuan Liu; Baole Li; Ran Zhang; Yingli Hao; Yuanyuan Pan; Na Li; Junfeng Kang (PLoS ONE, 2026)
Introduction The progression of Chronic gastritis seems to follow a pattern from chronic non-atrophic gastritis (CNAG) to chronic atrophic gastritis (CAG) to cancer, so it is particularly important to block key targets in disease progression. A gene that synthesizes secreted phospholipase A2, attracted our attention. Objectives To study whether phospholipase A2 group 10 (PLA2G10) in epithelial cells promote the progression of CNAG to CAG through the transforming growth factor-β (TGF-β) signaling. Methods We used RNA microarray and single-cell RNA sequencing datasets for bioinformatics analysis. The effects of PLA2G10 were verified by in vivo and in vitro experiments. The in vivo experiments used SD rats to establish a CNAG model for PLA2G10 and TGF-β intervention to observe the effects on gastric mucosal inflammation. In vitro experiments were conducted using human gastric mucosal epithelial cells (GES-1) for similar interventions. Results PLA2G10 inhibition led to the downregulation of TGF-β expression and attenuated the inflammatory response of the gastric mucosa. And the blockade of TGF-β signalling delayed the progression of CNAG to CAG, as evidenced by a reduction in inflammatory cell infiltration, a more regular cellular arrangement, and a reduction in collagen deposition. Conclusions Our study shows that PLA2G10 plays a key role in the progression of chronic gastritis and highlights the important role played by the TGF-β signalling pathway in this process.